Neural and neurocognitive markers of vulnerability to gambling disorder: a study of unaffected siblings - Limbrick-Oldfield, Eve H. (Neuropsychopharmacology, 2019)
Psychological and neurobiological markers in individuals with gambling disorder (GD) could reflect transdiagnostic vulnerability to addiction or neuroadaptive consequences of long-term gambling. Using an endophenotypic approach to identify vulnerability markers, we tested the biological relatives of cases with GD. Male participants seeking treatment for GD (n = 20) were compared with a male control group (n = 18). Biological siblings of cases with GD (n = 17, unrelated to the current GD group) were compared with a separate control group (n = 19) that overlapped partially with the GD control group. Participants completed a comprehensive assessment of clinical scales, neurocognitive functioning, and fMRI of unexpected financial reward. The GD group displayed elevated levels of self-report impulsivity and delay discounting, and increased risk-taking on the Cambridge Gamble Task. We did not observe impaired motor impulsivity on the stop-signal task. Siblings of GD showed some overlapping effects; namely, elevated impulsivity (negative urgency) and increased risk-taking on the Cambridge Gamble Task. We did not observe any differences in the neural response to win outcomes, either in the GD or sibling analysis compared with their control group. Within the GD group, activity in the thalamus and caudate correlated negatively with gambling severity. Increased impulsivity and risk-taking in GD are present in biological relatives of cases with GD, suggesting these markers may represent pre-existing vulnerability to GD.